Advances in Service and Industrial Robotics : Proceedings of the 27th International Conference on Robotics in Alpe-Adria Danube Region (RAAD 2018) /: Proceedings of the 27th International Conference on Robotics in Alpe-Adria Danube Region (RAAD 2018). (2018) - Unknown
No abstract available